2015
DOI: 10.13189/ujes.2015.030203
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Blades Slots on Rotating Stall Phenomenon in Centrifugal Blower

Abstract: Experimental and numerical investigations to study the effect of adding slots to the blades on the rotating stall phenomenon and pressure fluctuations in centrifugal blower. The experimental test rig which concludes a centrifugal blower, pressure sensors and measurement instrumentations are design and constructed for the present work. The experimental study has been carried out by measuring the static pressure variation and pressure fluctuation for two cases of impeller (with and without slots). Measuring of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The results of 2D numerical computations demonstrated that in the range of performance being investigated this is the most effective method of preventing occurrence of cavitation caused by loss of pressure. The prospect of utilising slots in the blades of centrifugal blowers was the subject of the investigation by Kassim, Saleh and Kadhum [6]. The results of the numerical and experimental investigations proved the positive effect of reducing pressure fluctuations during operation at sub-nominal flow rates.…”
Section: Submitting the Manuscriptmentioning
confidence: 99%
“…The results of 2D numerical computations demonstrated that in the range of performance being investigated this is the most effective method of preventing occurrence of cavitation caused by loss of pressure. The prospect of utilising slots in the blades of centrifugal blowers was the subject of the investigation by Kassim, Saleh and Kadhum [6]. The results of the numerical and experimental investigations proved the positive effect of reducing pressure fluctuations during operation at sub-nominal flow rates.…”
Section: Submitting the Manuscriptmentioning
confidence: 99%
“…Furthermore, detailed information on the flow field through the fan may be collected, providing guidance for fan impeller modification by cutting slots in the impeller blades. [5] investigated the effect of a cut slot in the blower blades, the results showed The magnitude of pressure variations decreases when slots are added to the impeller blades and the fluid poured through the slots into the impeller passages re-energizes the separated flow. [6] Studied the effect of constant-diameter slots in a perpendicular direction to the blade surface on radial fan impeller.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is characterized by the formation of a complex and turbulent flow pattern and the thickening of the boundary layer, which can lead to reduced fan efficiency and increased noise levels. The slots technique resolves this issue by injecting the flow from the pressure side of the blade to the suction side; these slots are installed close to the point of separation [2], [3] to regulate the formation of the boundary layer on the blade surface. The design of slot jet angle in the blade can have a significant impact on its performance, pressure distribution on the blade surface and impeller outlet.…”
Section: Introductionmentioning
confidence: 99%